Onset of the spring bloom in the northwestern Mediterranean Sea: influence of environmental pulse events on the in situ hourly-scale dynamics of the phytoplankton community structure - Thyssen, Melilotus; Grégori, Gerald J.; Grisoni, Jean-Michel; Pedrotti, Maria Luiza; Mousseau, Laure; Artigas, Luis F.; Marro, Sophie; Garcia, Nicole; Passafiume, Ornella; Denis, Michel J. (Frontiers in Microbiology, 2014)
Most of phytoplankton influence is barely understood at the sub meso scale and daily scale because of the lack of means to simultaneously assess phytoplankton functionality, dynamics and community structure. For a few years now, it has been possible to address this objective with an automated in situ high frequency sampling strategy. In order to study the influence of environmental short-term events (nutrients, wind speed, precipitation, solar radiation, temperature and salinity) on the onset of the phytoplankton bloom in the oligotrophic Bay of Villefranche-sur-Mer (NW Mediterranean Sea), a fully remotely controlled automated flow cytometer (CytoSense) was deployed on a solar-powered platform (EOL buoy, CNRS-Mobilis). The CytoSense carried out single-cell analyses on particles (1 to 800 µm in width, up to several mm in length), recording optical pulse shapes when analyzing several cm3. Samples were taken every two hours in the surface waters during two months. Up to 6 phytoplankton clusters were resolved based on their optical properties (PicoFLO, Picoeukaryotes, Nanophytoplankton, Microphytoplankton, HighSWS, HighFLO). Three main abundance pulses involving the 6 phytoplankton groups monitored indicated that the spring bloom not only depends on light and water column stability, but also on short-term events such as wind events and precipitation followed by nutrient pulses. Wind and precipitation were also determinant in the collapse of the clusters’ abundances. These events occurred within a couple of days, and phytoplankton abundance reacted within days. The third abundance pulse could be considered as the spring bloom commonly observed in the area. The high frequency data-set made it possible to study the phytoplankton cell cycle based on daily cycles of forward scatter and abundance. The combination of daily cell cycle, abundance trends and environmental pulses will open the way to the study of phytoplankton short-term reactivity to environmental conditions.